Challenges and Solutions for Inclusive Education in Primary Schools Literature Review - Yusli Yusli; Zohaib Hassan Sain (Lembaga Pendidikan Hikmatun Najah Blora, 2025)
Inclusive education in Elementary schools has become an urgent need to ensure access and quality education for all students, including those with special needs. This research aims to identify the challenges and solutions of inclusive education in elementary school through a literature review. The findings reveal that the primary challenges include a lack of teacher training, inadequate facilities, social stigma, and an inflexible curriculum. Proposed solutions encompass continuous teacher training, the provision of accessible infrastructure, community awareness campaigns, and a curriculum adapted to the diversity of students. This study concludes that inclusive education in elementary school requires collaboration among stakeholders, including schools, government, and communities, to create an equitable and supportive learning environment. The findings provide implications for educational policy in Indonesia to strengthen the implementation of inclusion at the primary level.